Disruptions in the hydrothermal water geochemistry inside Misti volcano in coincidence with the 8.4 Mw earthquake of June 23rd, 2001, in southern Peru - Cruz, Vicentina (2001)
Misti volcano (16°18'S, 71°24'W and 5822 in elevation) is located 17 km from Arequipa (-800000 inhabitants). It is characterized by two concentric summit craters. The youngest one hold lava dome, 130m wide, with fumarolic activity and temperature higuer than 200°C, geochemical techniques turn out to be very effective for the monitoring of active volcanoes. The ascent of a magmatic gases and their interactions with aquifers induce changes in the chemical composition and physical properties of the waters that can be sampled at the surface.The geochemical monitoring of the Misti volcano began in 1998 with a systematic sampling of the hot spring of "Charcani V", located to 6 Km of the active crater at 2960 meters in elevation.